2019
DOI: 10.1039/c9ra04680a
|View full text |Cite
|
Sign up to set email alerts
|

Percolation analysis of the electrical conductive network in a polymer nanocomposite by nanorod functionalization

Abstract: Chemical functionalization of nanofillers is an effective strategy to benefit the formation of the conductive network in the matrix which can enhance the electrical conductivity of polymer nanocomposites (PNCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The size and compactness of nets expectedly manage the efficient conductivity, for the reason that the conductive nets containing nanosheets and interphase pieces control the extent of electron shifting in nanocomposites [56][57][58] . The large nets provide the efficient transference of electrons, but the small nets weaken www.nature.com/scientificreports/ the electron moving.…”
Section: Examination Of Parametersmentioning
confidence: 99%
“…The size and compactness of nets expectedly manage the efficient conductivity, for the reason that the conductive nets containing nanosheets and interphase pieces control the extent of electron shifting in nanocomposites [56][57][58] . The large nets provide the efficient transference of electrons, but the small nets weaken www.nature.com/scientificreports/ the electron moving.…”
Section: Examination Of Parametersmentioning
confidence: 99%
“…Lebovka et al reported a two-step percolation in aggregating systems. It has been also reported that functionalization of fillers leads to a gradual breakdown of nanorods aggregation [93].…”
Section: Coupette Et Al Studied the Percolation Of Rigid Fractal Carb...mentioning
confidence: 99%